567 The Ever-Present Costs of Cosmetic Surgery Tourism; A 5-Year Observational Study. (4th May 2021) - Abed, H; Henry, N; Warner, R
Abstract: Introduction: Cosmetic surgery tourism is an ever-growing industry. An increasing number of patients are presenting to NHS services with complications from their surgery. This study aims to evaluate the current presentation patterns for complications in cosmetic surgery tourism, as well as the financial burden to a single UK level one trauma centre in Birmingham, UK. Method: Between 2015 and 2020, all patients presenting to the department of plastic surgery with complications of cosmetic surgery performed outside of the UK were included. A cost analysis was performed for each patient using published 'National Schedule of NHS Costs.' Results: A total of 26 patients presented to our hospital within the study period. 32 cosmetic procedures were undertaken, with the majority performed in Turkey (n = 14). Abdominoplasty was the most common procedure, followed by gluteal enhancement surgery. The total financial cost to our hospital from all cosmetic surgery-related complications was £152, 946, with an average cost per patient of £5, 882.54 (range £362 - £26, 585). Conclusions: Patients seek out medical tourism for multiple reasons. The costs displayed should predominantly be viewed as a reflection of the detrimental effect these complications can have on patients' lives. Global governing bodies should focus efforts on educating patients and raising awareness on this ever-prevalent issue.